2018
DOI: 10.1121/1.5051453
|View full text |Cite
|
Sign up to set email alerts
|

A measuring instrument for the auditory perception of rooms: The Room Acoustical Quality Inventory (RAQI)

Abstract: With the Room Acoustical Quality Inventory (RAQI), a measuring instrument for the perceptual space of performance venues for music and speech has been developed. First, a focus group with room acoustical experts determined relevant aspects of room acoustical impression in the form of a comprehensive list of 50 uni- and bipolar items in different categories. Then, n = 190 subjects rated their acoustical impression of 35 binaurally simulated rooms from 2 listening positions, with symphonic orchestra, solo trumpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
2
14
0
1
Order By: Relevance
“…Similarly, a relationship between ASW and the sound pressure level was also acknowledged by Morimoto et.al [51]. A correlation between width, loudness and the source size was also reported by Weinzierl et al [15], supporting the hypothesis that ASW perception is indeed influenced by the sound strength. However, other studies in the context of concert hall acoustics confirmed the IACC Early and Lf as well as [1-IACC E3] (a.k.a.…”
Section: Multi-dimensionality Of Apparent Source Width (Asw)supporting
confidence: 70%
See 2 more Smart Citations
“…Similarly, a relationship between ASW and the sound pressure level was also acknowledged by Morimoto et.al [51]. A correlation between width, loudness and the source size was also reported by Weinzierl et al [15], supporting the hypothesis that ASW perception is indeed influenced by the sound strength. However, other studies in the context of concert hall acoustics confirmed the IACC Early and Lf as well as [1-IACC E3] (a.k.a.…”
Section: Multi-dimensionality Of Apparent Source Width (Asw)supporting
confidence: 70%
“…Weinzierl et al [15], in a comprehensive study using computer simulations of multiple acoustic venues and various types of sound sources, developed an instrument aimed towards measuring the perception of performance spaces. A number of perceptual attributes were elicited from focus group discussions on audible differences among the concert halls.…”
Section: Multi-dimensionality Of Spatial Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the ability to recognize different rooms by their acoustics has received very little attention, and in the authors' knowledge, there is no direct precedence for the current experiment. In the development of the room acoustic quality inventory, Weinzierl et al (2018) concluded that "…listeners are obviously able to identify the room and its acoustical properties as a consistent cognitive object." The current study has now put this abstract statement on an empirical basis, but according to the evidence here, the recognition of rooms by their acoustic properties seems to be rather elusive and approximate, especially when room acoustics are perceived in variable sound contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In singing voice pedagogy, the concept of chiaroscuro, or bright-dark tone, is central to the bel canto style, describing the ideal singing voice as having "a bright edge as well as a dark round quality in a complex texture of vocal resonances" (Stark, 2003, p. 33). Timbral brightness has also been shown to be an important factor in assessing concert hall acoustics (Lokki et al, 2011;Weinzierl et al, 2018). Despite the major role of brightness in music creation and perception, research has not yet delineated its detailed perceptual and cognitive structure.…”
Section: Introductionmentioning
confidence: 99%